PENGHANCURAN INFRASTUKTUR DAN SANITASI AIR DI KHAN YOUNIS-GAZA SELATAN SEBAGAI ELEMENTS OF CRIME BERDASARKAN HUKUM HUMANITER INTERNASIONAL: Destruction of Water Infrastructure and Water Sanitation in Khan Yunis-South Gaza as Elements of Crime Under International Humanitarian Law - R Halya Zayna Fajwa; Arlina Permanasari (Reformasi Hukum Trisakti, 2025)
The destruction of water infrastructure and sanitation was carried out by the Israeli military in the armed conflict in Khan-Yunis South Gaza on an ongoing basis, including using starvation tactics against Palestinians there. The formulation of this research problem, namely: Is the destruction of water infrastructure and sanitation in Khan Yunis-South Gaza by Israel a war crime under international humanitarian law? The method used is normative juridical, descriptive analysis, using secondary data, data collection through literature study, data analysed qualitatively, and deductive conclusion. The results of the discussion and conclusions show that Israel's actions to destroy infrastructure and water sanitation are a violation of the principle of distinction and the principle of humanity, also using famine tactics so that these things are war crimes.